Evidence for the Role of B Cells and Immunoglobulins in the Pathogenesis of Multiple Sclerosis. (4th August 2011) - Wootla, Bharath; Denic, Aleksandar; Keegan, B. Mark; Winters, Jeffrey L.; Astapenko, David; Warrington, Arthur E.; Bieber, Allan J.; Rodriguez, Moses
Abstract : The pathogenesis of multiple sclerosis (MS) remains elusive. Recent reports advocate greater involvement of B cells and immunoglobulins in the initiation and propagation of MS lesions at different stages of their ontogeny. The key role of B cells and immunoglobulins in pathogenesis was initially identified by studies in which patients whose fulminant attacks of demyelination did not respond to steroids experienced remarkable functional improvement following plasma exchange. The positive response to Rituximab in Phase II clinical trials of relapsing-remitting MS confirms the role of B cells. The critical question is how B cells contribute to MS. In this paper, we discuss both the deleterious and the beneficial roles of B cells and immunoglobulins in MS lesions. We provide alternative hypotheses to explain both damaging and protective antibody responses.